Pioglitazone Ameliorates Gentamicin Ototoxicity by Affecting the TLR and STAT Pathways in the Early Postnatal Organ of Corti - Sekulic-Jablanovic, Marijana; Wright, Matthew B.; Petkovic, Vesna; Bodmer, Daniel (Frontiers in Cellular Neuroscience, 2020)
Noise trauma, infection and ototoxic drugs are frequent external causes of hearing loss. With no pharmacological treatments currently available, understanding the mechanisms and pathways leading to auditory hair cell damage and repair is crucial for identifying potential pharmacological targets. Prior research has implicated increased reactive oxygen species and inflammation as general mechanisms of hearing loss common to diverse causes. Novel targets of these two key mechanisms of auditory damage may provide new paths toward prevention and treatment of hearing loss. Pioglitazone, an oral antidiabetic drug from the class of thiazolidinediones, acts as an agonist of the peroxisome proliferator-activated receptor gamma (PPAR-γ) and is involved in regulation of lipid and glucose metabolism. PPAR-γ is an important player in repressing expression of inflammatory cytokines and signaling molecules. We evaluated the effects of pioglitazone in mouse organ of Corti explants to characterize its influence on signaling pathways involved in auditory hair cell damage. Organ of Corti explants were cultured with pioglitazone, gentamicin, or a combination of both agents. Pioglitazone treatment resulted in a significant repression of interferon (IFN)-alpha and -gamma pathways and downstream cytokines, as assessed by RNA sequencing and quantitative PCR gene expression assays. More detailed investigation at the single gene and protein level showed that pioglitazone mediated its anti-inflammatory effects through alterations of the Toll-like receptor (TLR) and STAT pathways. Together, these results indicate that pioglitazone significantly represses IFN and TLR in the cochlea, dampening the activity of gentamicin-induced pathways. These data support our previous results demonstrating significant protection of auditory hair cells in organ of Corti explants exposed to pioglitazone and other PPAR-targeted agents.